Copper zinc tin sulfide thin films for photovoltaics synthesis and characterisation by electrochemical methods - Scragg, Jonathan J. (Springer theses., 2011)
Jonathan Scragg documents his work on a very promising material suitable for use in solar cells. Copper Zinc Tin Sulfide (CZTS) is a low cost, earth-abundant material suitable for large scale deployment in photovoltaics. Jonathan pioneered and optimized a low cost route to this material involving electroplating of the three metals concerned, followed by rapid thermal processing (RTP) in sulfur vapour. His beautifully detailed RTP studies -- combined with techniques such as XRD, EDX and Raman -- reveal the complex relationships between composition, processing and photovoltaic performance. This exceptional thesis contributes to the development of clean, sustainable and alternative sources of energy.